(untitled) (mathematica didactica, 2004)
Geometric constructions in the virtual space with Cabri 3D open up new possibilities to treat classic spatial geometric topics. This contribution about the analogical processing of specific lines and points of the triangle to corresponding objects of the tetrahedron shows how to support the discovery of analogies with the dynamic 3D-system and how to make them really accessible for the students.